A LEGIMIDADE ATIVA NAS AÇÕES COLETIVAS JUSTRABALHISTAS E O COMBATE AO TRABALHO ESCRAVO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
“With the intention of participating in the “XI Brazilian Congress of Collective Process and Citizenship”, of the 75th Legal Week, of Unaerp, through this article, under the title “The Active Legitimacy of Collective Actions Justrabalhistas and the Combat against Slave Labor”, even though Briefly, we want to present the historical evolution of formal sources, clarify the concept of contemporary slave labor, point out the active legitimacy among the interests that can be protected in collective labor actions, and then bring the theoretical text closer to the practical issues with which Courts, institutions and society have been struggling to understand the dimension of the collective labor process and its importance in combating slave labor and inequalities.”